Pengembangan Flipbook Tradisibuku (Sastra Legenda Literasi Budaya Kudus) Untuk Meningkatkan Kemampuan Membaca Pemahaman Siswa Kelas IV - Rani Setiawaty; Fatikhatun Najikhah; Leony Kristiyani; Sinta Andayani; Roslita Anggraeni (Journal Prakarsa Paedagogia, 2025)
This research aims to develop an interactive flipbook learning medium named TRADISIBUKU (Kudus Cultural Literacy through Legend Stories) to enhance the reading comprehension abilities of fourth-grade students at SD 1 Gondangmanis. This developmental research employs the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects comprised 8 fourth-grade students from SD 1 Gondangmanis. Data were collected through interviews, questionnaires, and tests (pre-test and post-test). Validation results from media experts and material experts indicated that the TRADISIBUKU flipbook is highly feasible and good for use as a learning medium, receiving positive responses from the teacher. Small-scale trials demonstrated an improvement in students' reading comprehension, evidenced by an average N-Gain score of 0.6063 (60.63%), categorized as "medium". This suggests that the TRADISIBUKU flipbook is quite effective in improving students' learning outcomes and has the potential to be an engaging and culturally relevant learning tool. For further development, it is recommended to conduct large-scale trials and incorporate interactive game features.